UNRESOLVED ISSUES OF INITIAL TREATMENT OF PARTIAL EPILEPSY - L. V. Lipatova (Эпилепсия и пароксизмальные состояния)
Abstract: the selection principles for antiepileptic drugs choice for the initial treatment of partial seizures in epileptic patients with newly diagnosed or untreated epilepsy are discussed; evidence-based criteria and opportunities of the personalized therapy of AED therapy are argued in the review.